Imbursement Array in Dental Practice Management A Review - Khare, Anshika; Gupta, Ankita (Journal of Orofacial Research, 2018)
Dentistry is a dignified healthcare profession but due to transient transformation in dental practice, dentistry has reached to its peak level. The main barrier to cater the dental services throughout all area including rural and urban is financial which has to be removed. Thus, to maintain the glory of the profession and to reach the people at their doorsteps, proper practice management of finance in terms of payment is very important. We present a review on imbursement array in dental practice management which was obtained from the literature search of published articles, online manuals and books.